Philosophy of Islamic Education from The Perspective of Ali Ahmad Madkur: A Critical Analysis - Setiawan, Andry; Musthafa, Izzudin; Hambali, Adang (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2024)
This article employs a critical analysis method to elucidate Ali Ahmad Madkur's views on the philosophy of Islamic education. In this study, we delve into an in-depth analysis of his writings and thoughts, focusing on philosophical concepts he deems controversial. Madkur's seemingly antipathetic stance toward the philosophy of Islamic education is expounded, emphasizing the potential deviation of pure Islamic values through the application of philosophical concepts. The research method encompasses literature review and analysis of Madkur's primary texts. We also consider the practical consequences of Madkur's views on the implementation of Islamic education. In the context of constructive dialogue and continuous reflection, this article provides space for understanding different perspectives and encourages profound considerations regarding the integration of Islamic values with contemporary educational needs.